Understanding the Central Location of a Hexagonal Hole in a B36 Cluster - Liu, Lei; Osorio, Edison; Heine, Thomas (Chemistry - An Asian Journal, 2016)
The most stable form of a B36 cluster has a central hexagonal hole. Such an interesting finding has led to the possible synthesis of a 2D boron sheet by employing the B36 cluster as the building unit. Herein, a DFT study to investigate the reason for the central location of the hexagonal hole in the B36 cluster is presented. The results show that the B36 cluster with a central hexagonal hole is highly thermodynamically and kinetically stable. More importantly, such high stability is further understood through chemical bonding analysis.
CRIS-Team Scopus Importer:2023-03-20
Keywords: boron clusters; chemical bonding; density functional theory calculations; hexagonal hole